Alexithymia and its Association with Smartphone Addiction and Physical Activity in University Students of Islamabad - Kashaf Nadeem, Tehreem, Ibraheem Zafar, Naveed Ahmad, Ramsha Masood, Muhammad Saad Shafique, Ashar Rafi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Determine the prevalence of alexithymia and its relationship with smartphone addiction and physical activity among university students of Islamabad. Methods: In this cross sectional study, a 20 item Toronto Alexithymia Scale (TAS-20), Smartphone Addiction Scale-Long version (SAS-LV), and International Physical Activity Questionnaire-Short form (IPAQ-SF) were administered to 377 students from 6 universities of Islamabad using convenient sampling technique and the data was analyzed through statistical package for social sciences 26. Results: Alexithymia was present in 29.7% of university students and it was positively correlated with smartphone addiction but not significantly associated with physical activity. The two factors in the subscales of alexithymia DIF and DDF were positively correlated with smartphone addiction whereas EOT was not significantly correlated. Moreover, other sociodemographic variables showed a positive relationship with alexithymia: age, gender, satisfaction with life and residential status. Practical implications: This study would increase the awareness about alexithymia and its associated factors in the local community which would further steer direction to seek help from healthcare practitioners. Conclusion: More than 1/4rth of the university students were suffering from alexithymia and the score of alexithymia increased with level of smartphone addiction. Keywords: Alexithymia, University students, Islamabad, Smartphone Addiction Scale-Long version, International Physical activity questionnaire.